2009
DOI: 10.1007/s12149-009-0315-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of myocardial perfusion SPECT images in combination with the maximal heart rate at exercise testing in Japanese patients with suspected ischemic heart disease: a sub-analysis of J-ACCESS

Abstract: The combination of SSS using Ex-SPECT and the maximal heart rate is a useful predictor of cardiac events in patients with suspected coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
6
1
Order By: Relevance
“…The utility of SSS score is also established as the prognostic predictors of the cardiac events for decades [11][12][13]. Base on the J-ACCESS study, SSS category most useful predictor for cardiac events in Japanese populations [5,10,14,15]. However, in this present study, it was not a significant predictor for both cardiac hard events and cardiac major events by Cox multivariate regression analysis in patients who have the submaximal exercise.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The utility of SSS score is also established as the prognostic predictors of the cardiac events for decades [11][12][13]. Base on the J-ACCESS study, SSS category most useful predictor for cardiac events in Japanese populations [5,10,14,15]. However, in this present study, it was not a significant predictor for both cardiac hard events and cardiac major events by Cox multivariate regression analysis in patients who have the submaximal exercise.…”
Section: Discussioncontrasting
confidence: 51%
“…ity in exercise test because of a tendency earlier stopping the exercise by leg fatigue before reaching the target heart rates. In the sub-study in J-ACCESS Ueshima et al reported SSS score and the maximal heart rate were independent predictors of cardiac major events [15]. The reason of different results between our and their studies might be that they initially classified the patient groups according to SSS score and heart rate score, and excluded the patients who took ␤-blockers from the analysis.…”
Section: Discussionmentioning
confidence: 57%
“…In the J-ACCESS 3 study examining patients with an eGFR<50 ml/min/1.73 m 2 , a lower eGFR, a higher CRP, and a higher SSS using MPI was a strong predictor of prognosis in CKD patients (6). Based on the J-ACCESS study, SSS was also the most useful predictor for cardiac events in the Japanese population (12)(13)(14). In the present study, moderate to severe transient ischemia (SSS>8) predicted cardiac events ACE-I: angiotensin-converting inhibitor, ARB: angiotensin receptor blocker, BMI: body mass index, CRP: Creactive protein, ESV: end-systolic volume, EDV: end-diastolic volume, LVEF: left ventricular ejection fraction, eGFR: glomerular filtration rate, HbA1c: hemoglobin A1c, HDL-C: high-density lipoprotein cholesterol, LDL-C: low-density lipoprotein cholesterol, PAD: peripheral artery disease, SDS: summed difference score, SRS: summed rest score, SSS: summed stress score was also within the assumption.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the independent variables for cardiac events, we then used multivariate logistic regression modeling with the stepwise method to examine the association of car-diovascular events with some modulator which the probability of reported risk factors (eGFR, CRP, SSS, LVEF, ESV, EDV) and aortic calcification. These indicators were established in the J-ACCESS study and currently used broadly with software named 'Heart Risk View' to estimate the cardiac events(12)(13)(14)(15). Because this present study was a sub-analysis of J-ACCESS 3, the analysis was performed using the numerical values from the original J-ACCESS 3 study.…”
mentioning
confidence: 99%
“…The 3-year major event rates in patients with SSS <4 who achieved target heart rates or not were 1.4% and 2.4%, respectively, compared with 4.0% and 5.4%, respectively, in those with SSS ≥4. 19 The absolute peak exercise capacity in a treadmill test of 6,213 consecutive men was a powerful predictor of the risk of death. 20 Similarly, patients with positive ischemic ECG changes and reversible perfusion abnormalities had higher rates of hard and major events.…”
Section: Exercise Tolerance and Ecg Changesmentioning
confidence: 99%